Effect of robot-assisted gait training on gait automaticity in Parkinson disease: A prospective, open-label, single-arm, pilot study. Issue 5 (5th February 2021) - Yun, Seo Jung; Lee, Hyun Haeng; Lee, Woo Hyung; Lee, Seung Hak; Oh, Byung-Mo; Seo, Han Gil
Abstract : Abstract: Gait automaticity is reduced in patients with Parkinson disease (PD) due to impaired habitual control. The aim of this study was to investigate the effect of robot-assisted gait training (RAGT) on gait automaticity as well as gait speed and balance in patients with PD. This study was a prospective, open-label, single-arm, pilot study. We planned to recruit 12 patients with idiopathic PD. Participants received 12 sessions of RAGT using exoskeleton-type robotic device. Sessions were 45-minute each, 3 days a week, for 4 consecutive weeks using an exoskeleton-type gait robot. The primary outcome was the percentage of dual-task interference measured by the 10-Meter Walk Test (10MWT) under single and dual-task (cognitive and physical) conditions. Secondary outcomes were the Berg Balance Scale and Korean version of the Falls Efficacy Scale-International. All measures were evaluated before treatment (T0), after treatment (T1), and 1-month post-treatment (T2). Twelve patients were enrolled and 1 dropped out. Finally, 11 patients with idiopathic PD were analyzed. The mean age of 11 patients (5 males) was 66.46 ± 5.66 years, and disease duration was 112.91 ± 50.19 months. The Hoehn and Yahr stages were 2.5 in 8 patients and 3 in 3 patients. Linear mixed-effect model analysis showed a significant change over time only in single-task gait speed of the 10MWT ( P = .007), but not in dual-task gait speed, dual-task interferences, and Korean version of the Falls Efficacy Scale-International. Cognitive dual-task interference significantly increased ( P = .026) at T1, but not at T2 ( P = .203). No significant changes were observed for physical dual-task interference at T1 and T2. Single-task gait speed of the 10MWT was significantly increased at T1 ( P = .041), but not at T2 ( P = .445). There were no significant changes in the dual-task gait speed of 10MWT. A significant improvement was observed in Berg Balance Scale score at T1 and T2 ( P = .004 and P = .024, respectively). In this pilot study, despite improvement in walking speed and balance, gait automaticity in patients with PD was not improved by RAGT using an exoskeleton-type robot. Additional therapeutic components may be needed to improve gait automaticity using RAGT in patients with PD.